The Segmented Zambezi Sedimentary System from Source to Sink: 1. Sand Petrology and Heavy Minerals - (:unkn) unknown (My University, 2021)
The Zambezi River rises at the center of southern Africa, flows across the low-relief Kalahari Plateau, meets Karoo basalt, plunges into Victoria Falls, follows along Karoo rifts, and pierces through Precambrian basement to eventually deliver its load onto the Mozambican passive margin. Reflecting its polyphase evolution, the river is subdivided into segments with different geological and geomorphological character, a subdivision finally fixed by man’s construction of large reservoirs and faithfully testified by sharp changes in sediment composition. Pure quartzose sand recycled from Kalahari desert dunes in the uppermost tract is next progressively enriched in basaltic rock fragments and clinopyroxene. Sediment load is renewed first downstream of Lake Kariba and next downstream of Lake Cahora Bassa, documenting a stepwise decrease in quartz and durable heavy minerals. Composition becomes quartzo-feldspathic in the lower tract, where most sediment is supplied by high-grade basements rejuvenated by the southward propagation of the East African rift. Feldspar abundance in Lower Zambezi sand has no equivalent among big rivers on Earth and far exceeds that in sediments of the northern delta, shelf, and slope, revealing that provenance signals from the upper reaches have ceased to be transmitted across the routing system after closure of the big dams. This high-resolution petrologic study of Zambezi sand allows us to critically reconsider several dogmas, such as the supposed increase of mineralogical “maturity” during long-distance fluvial transport, and forges a key to unlock the rich information stored in sedimentary archives, with the ultimate goal to accurately reconstruct the evolution of this mighty river flowing across changing African landscapes since the late Mesozoic.
Keywords: African Research